Bacteriophage and Bacterial Susceptibility, Resistance, and Tolerance to Antibiotics - Qingquan Chen; Tejas Dharmaraj; Pamela C. Cai; Elizabeth B. Burgener; Naomi L. Haddock; Andy J. Spakowitz; Paul L. Bollyky (MDPI AG, 2022)
Bacteriophages, viruses that infect and replicate within bacteria, impact bacterial responses to antibiotics in complex ways. Recent studies using lytic bacteriophages to treat bacterial infections (phage therapy) demonstrate that phages can promote susceptibility to chemical antibiotics and that phage/antibiotic synergy is possible. However, both lytic and lysogenic bacteriophages can contribute to antimicrobial resistance. In particular, some phages mediate the horizontal transfer of antibiotic resistance genes between bacteria via transduction and other mechanisms. In addition, chronic infection filamentous phages can promote antimicrobial tolerance, the ability of bacteria to persist in the face of antibiotics. In particular, filamentous phages serve as structural elements in bacterial biofilms and prevent the penetration of antibiotics. Over time, these contributions to antibiotic tolerance favor the selection of resistance clones. Here, we review recent insights into bacteriophage contributions to antibiotic susceptibility, resistance, and tolerance. We discuss the mechanisms involved in these effects and address their impact on bacterial fitness.